N-Acetylcysteine and Atherosclerosis: Promises and Challenges - Yuqi Cui; Qiang Zhu; Hong Hao; Gregory C. Flaker; Zhenguo Liu (Antioxidants, 2023)
Atherosclerosis remains a leading cause of cardiovascular diseases. Although the mechanism for atherosclerosis is complex and has not been fully understood, inflammation and oxidative stress play a critical role in the development and progression of atherosclerosis. N-acetylcysteine (NAC) has been used as a mucolytic agent and an antidote for acetaminophen overdose with a well-established safety profile. NAC has antioxidant and anti-inflammatory effects through multiple mechanisms, including an increase in the intracellular glutathione level and an attenuation of the nuclear factor kappa-B mediated production of inflammatory cytokines like tumor necrosis factor-alpha and interleukins. Numerous animal studies have demonstrated that NAC significantly decreases the development and progression of atherosclerosis. However, the data on the outcomes of clinical studies in patients with atherosclerosis have been limited and inconsistent. The purpose of this review is to summarize the data on the effect of NAC on atherosclerosis from both pre-clinical and clinical studies and discuss the potential mechanisms of action of NAC on atherosclerosis, as well as challenges in the field.